The development of baiting system was very advanced, however it was very expensive thus the use of it was limited on certain community. Based on those conditions, it was needed a researches on local resourches basis or low cost material baiting system in order to be applicated in building protection included simple home. This researches consisted of laboratory and field test. The laboratory test was performed to determine preference baiting media (pulp, sawdust, Pinus merkusii wood, WMD (wood mo - Yudi RISMAYADI; ARINANA . (Jurnal Ilmu dan Teknologi Hasil Hutan, 2009)
The development of baiting system was very advanced, however it was very expensive thus the use of it was limited on certain community. Based on those conditions, it was needed a researches on local resourches basis or low cost material baiting system in order to be applicated in building protection included simple home. This researches consisted of laboratory and field test. The laboratory test was performed to determine preference baiting media (pulp, sawdust, Pinus merkusii wood, WMD (wood monitoring devices) from Pinus radiata and reliability tested between disodium borax decahydrate and chitosan against Coptotermes curvignathus. After the determination of baiting system and reliability, field test was performed on termite attacked building. Field test consisted of termite presence detection,observatory station, determination of consumption rate and baiting system resistance. The laboratory results showed the most preference baiting system was WMD with persentage weight loss was 40.5%. The comparation of reliability between disodium borax decahydrate and chitosan showed that termite mortality of disodium borax decahydrate was higher than chitosan, meanwhile reliability results showed oltherwise. Chitosan field test showed eating consumption level was decreasing at 75th days and on 135th days eating consumption level was rached 15 gr/day. It meaned there was a decreasing of termite population cause of termite baiting system.   Keywords :  Pulp, disodium borax, chitosan, baiting, Coptotermes curvignathus